SOCIO-PHILOSOPHICAL METHODS OF IMPROVING PROFESSIONAL ETHICS OF INTERNAL AFFAIRS EMPLOYEES - Usmonova Ozoda Xoldorovna (PEDAGOGS, 2024)
Abstract: This article presents the factors of formation of the professional culture of the employees of the internal affairs bodies, professional ethics, culture of behavior, rules of behavior, conditions for forming a psychological portrait and the obligations that each employee must follow.